Buyer preferences for sheep and goats in southern Nigeria: A hedonic price analysis - Jabbar, M.A. (Wiley, 1998)
A survey of two rural markets in southwest Nigeria over 14 months showed that supplies, sales and prices of sheep and goats varied widely during the period with a sharp peak during the Muslim festival of Eid-el-Kabir and a smaller peak during the Christmas-New Year period. Local West African Dward (WAD) sheep and goats and northern Y'ankasa sheep and Red Sokoto goats were traded in the markets and animals were purchased for rearing, trading, ceremonies, butchering/catering, sacrifice, and festivals. There were significant differences between species/breeds purchased for various purposes. A hedonic price model was fitted to determine factors influencing price. After adjustments were made for age, weight, sex, time of transaction and market, WAD sheep commanded higher prices than WAD goats and Red Sokoto goats for all purposes except for butchering/catering; Red Sokoto goats commanded similar or lower prices than WAD goats depending on the purpose for purchase; and Y'ankasa sheep, principally purchased for the Eid-el-Kabir festival, commanded marginally higher prices than WAD sheeThe market share of WAD sheep is currently small and is under competition from northen sheep and goats, so increased production of WAD sheep in the south will benefit both producers and consumers in the area. In general, the results indicate that buyers have preferences for specific breeds and species for specific purposes, so producers and sellers may benefit by targeting specific buyer categories and times of the year. Published by Elsevier Science B.V.